4x+5=-x+8+5x-3

Simple and best practice solution for 4x+5=-x+8+5x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+5=-x+8+5x-3 equation:


Simplifying
4x + 5 = -1x + 8 + 5x + -3

Reorder the terms:
5 + 4x = -1x + 8 + 5x + -3

Reorder the terms:
5 + 4x = 8 + -3 + -1x + 5x

Combine like terms: 8 + -3 = 5
5 + 4x = 5 + -1x + 5x

Combine like terms: -1x + 5x = 4x
5 + 4x = 5 + 4x

Add '-5' to each side of the equation.
5 + -5 + 4x = 5 + -5 + 4x

Combine like terms: 5 + -5 = 0
0 + 4x = 5 + -5 + 4x
4x = 5 + -5 + 4x

Combine like terms: 5 + -5 = 0
4x = 0 + 4x
4x = 4x

Add '-4x' to each side of the equation.
4x + -4x = 4x + -4x

Combine like terms: 4x + -4x = 0
0 = 4x + -4x

Combine like terms: 4x + -4x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 3f+g=-14 | | x-6+7=26(x+7) | | 7*8-6+3=47 | | S+k+m=180 | | -2x(x+4)+6=-3 | | (3a+7)+(2a-6)=(-9) | | 2(-5+v)=-4 | | v^2+14v=19 | | -8=-6x-3 | | 17=w | | 12=4+6m | | G(x)=3f(x-2)-4 | | 7T+2=12+5T | | 12=10x+2x | | -2(6n-8)=16-12n | | 4k+7=-4 | | 7K+-8K+-5K= | | 8x-2=-9+nx | | x-.55x=0 | | 1=-15+8x | | 12=1.5 | | 2(3x-5)=9-(2x-5) | | 0.2x-6=x | | 2(5d+3)=4d | | -5.6+12.2=5h | | 4(m-3)=-32 | | 4x+6x+1=0 | | x^2-5=sqrt(3*x) | | -23-2p=19-p | | 12x^2+35x-3=0 | | 7=9(2f+5) | | 3(2x+3)=4-x |

Equations solver categories